Democracy, media and law in Malaysia and Singapore : a space for speech - Kenyon, Andrew T.; Marjoribanks, Timothy, 1965-; Whiting, Amanda (Abingdon, Oxon : Routledge, 2014)
'This book explores these issues with reference to Malaysia and Singapore. It analyses how journalists monitor governments and cover elections, discussing what difference journalism makes; it examines citizen journalism, and the constraints on it, often self-imposed constraints; and it assesses how governments control the media, including outlining the development and current application of legal restrictions'--
Includes bibliographical references and index.
Keywords: Government and the press -- Malaysia; Government and the press -- Singapore; Journalism -- Political aspects -- Malaysia; Journalism -- Political aspects -- Singapore; Mass media -- Law and legislation -- Malaysia; Mass media -- Law and legislation -- Singapore